Empowered Educators in China: How High-Performing Systems Shape Teaching Quality - Sato, Mistilina (Jossey-Bass, 2017)
BEST PRACTICES FROM CHINA'S HIGH-PERFORMING SCHOOL SYSTEM Empowered Educators in China is one volume in a series that explores how high-performing educational systems from around the world achieve strong results. The anchor book, Empowered Educators: How High-Performing Systems Shape Teaching Quality Around the World, is written by Linda Darling-Hammond and colleagues, with contributions from the author of this volume. Empowered Educators in China describes the nation's policy reforms that built the modern Chinese educational system and the educational practices that are considered typical in China. The book spotlights Shanghai's system which is distinctive and superior. Shanghai offers a clear illustration of an educational system that continually invests in educating a diverse student population and, by measures of international comparison tests, is achieving outstanding results. Many factors contribute to the Shanghai system's ongoing success, including the students' motivation toward strong performance, the parental support for education that is culturally ingrained throughout the country, the focus that teachers place on high expectations for students, and the individual tutoring they provide. The author argues that these factors are only a partial explanation of Shanghai's success and then closely describes educational policies that support teachers' preparation, hiring, ongoing development, and opportunities for awards and leadership. These policies are based on the assumption that teachers are key to the nation's future and must be appropriately supported in order to contribute to student performance and achievement, an assumption that is also explicitly stated within Chinese law. This volume offers specific descriptions of how these national policies are translated, adapted, and enacted in Shanghai.